Prevalence of deep vein thrombosis and pulmonary embolism in superficial thrombophlebitis of the lower limbs: prospective study of 60 cases - Sobreira, Marcone Lima [UNESP]; Maffei, Francisco Humberto de Abreu [UNESP]; Yoshida, Winston Bonetti [UNESP]; Rollo, Hamilton Almeida [UNESP]; Lastoria, S. [UNESP]; Griva, B. Lotufo [UNESP]; De Carvalho, L. Raquel [UNESP] (Edizioni Minerva Medica, 2009)
Aim. Superficial thrombophlebitis (ST) ascending the lower limbs is a common disease, which may be associated with deep vein thrombosis (DVT) and pulmonary embolism (PE). The aim of this study was to investigate the prevalence of DVT and PE as complications of ascending ST of the lower limbs in the great saphenous vein (GSV) or SSV (SSV) and probable risk factors.Methods. For this study 60 consecutive patients were enrolled with ascending ST of the GSV or SSV, seen between 2000 and 2003 at a public hospital in Botucatu, SP, Brazil. All patients were assessed clinically, by venous Duplex scanning of the lower limbs to confirm ST and test for DVT, and by means of pulmonary scintigraphy to test for PE.Results. In 13 ST cases (21.67%) there was concomitant DVT and 17 ST patients (28.33%) also had PE. Eleven patients had a clinical status suggestive of DVT, but only in eight of these (61.5%), this clinical diagnosis was confirmed. Fourteen patients had a clinical status suggestive of PE, and this diagnosis was confirmed in six cases (35.30%). ST patients who also had DVT and/or PE were given anticoagulant treatment with heparin and warfarin. None of the variables studied was predictive of DVT or PE (P>0.05). However, the presence of varicose veins reduced the risk of patients having DVT (relative risk=9.09; 95%CI:1.75 - 50.00 and P=0.023).Conclusion. The prevalence rates of PE (28.3%) and DVT (21.6%) were elevated in this sample of ascending ST cases, indicating a need for detailed assessment of patients for signs of these complications, including for therapeutic management decision making. [Int Angiol 2009;28:400-8]
Keywords: Pulmonary embolism; Thrombophlebitis; Venous thrombosis